The impact of a modified microbiota-accessible carbohydrate diet on gut microbiome and clinical symptoms in colorectal cancer patients following surgical resection - Kim, Boyeon; Lee, Jiwon; Jung, Eun Sung; Lee, Sunyoung; Suh, Dong Ho; Park, Yu Jin; Kim, Jin; Kwak, Jung-Myun; Lee, Soohyeon (Frontiers in Microbiology, 2024)
A high-fiber diet is widely recognized for its positive effects on the gut microbiome. However, the specific impact of a high-fiber diet on the gut microbiome and bowel habits of patients with colon cancer remains poorly understood. In this study, we aimed to assess the effects of a modified microbiota-accessible carbohydrate (mMAC) diet on gut microbiota composition and clinical symptoms in colon cancer patients who underwent surgical resection. To achieve this, we enrolled 40 patients in two groups: those who received adjuvant chemotherapy and those who did not. Fecal samples were collected before and after dietary interventions for microbial and metabolite analyses. Each group was randomized in a 1:1 ratio to follow either a 3-week conventional diet followed by a 3-week mMAC diet, or the reverse sequence. Although there were no significant differences in the microbial diversity data before and after the mMAC diet in both the non-chemotherapy and chemotherapy groups, distinct differences in gut microbial composition were revealed after the mMAC diet. Specifically, the abundance of Prevotella, which is associated with high-fiber diets, was further elevated with increased concentrations of acetate and propionate after the mMAC diet. Additionally, patients who experienced improved diarrhea and constipation after the mMAC diet exhibited an enrichment of beneficial bacteria and notable changes in metabolites. In conclusion, this study provides valuable insights into the potential benefits of the mMAC diet, specifically its impact on the gut microbiome and clinical symptoms in postoperative colorectal cancer (CRC) patients. These findings emphasize the potential role of a high-fiber diet in influencing the gut microbiome, and the clinical symptoms warrant further investigation.